Growth Status and Glycemic Control of Diabetic Children in a Tertiary Care Hospital in Dhaka City (Mugda Medical College Journal, 2024)
Childhood growth is a critical indicator of the health status of a child which also determines the overall developmental potential in adult life. Along with an increased risk of developing various co-morbidities, diabetic children remain susceptible to growth delay in terms of height and weight. Thus it is necessary to evaluate their growth status about their glycemic control. This cross-sectional study observed 148 sequentially selected diabetic children aged 9 to 15 years, with 5 years of diabetes duration attending a tertiary level hospital. Data regarding their anthropometric measurements including height and weight, HbA1c status, and diabetic history has been collected. HbA1c level is a significant determinant of height, weight, and BMI of the study subjects (p0.05) although it was significantly associated with their HbA1c level (p